2012
DOI: 10.1016/j.jocd.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bone Status in High-Level Cyclists

Abstract: The purpose of this study was to evaluate the bone status in highly trained professional cyclists subjected to regular training and tough competitions. Bone mineral density (BMD) was measured at different regions of interest by dual X-ray absorptiometry and main biological parameters related to bone metabolism were obtained in 29 cyclists. Lumbar BMD was 0.94±0.01 g/cm² (Z score=-1.28±0.07) and 1 cyclist out of 4 had and abnormally low value (Z-score <-2). The mean Z score at the total femoral site was-1.22±0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The lumbar spine has probably been the most studied region in this regard, with fairly conclusive results that lower BMD can be observed in cyclists compared with controls [29-35], practitioners of other sports [19,35-37] or reference values [4,38,39]. Moreover, the pelvic and hip regions, as key areas for osteoporotic fractures, and the whole body have been studied with concerning results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lumbar spine has probably been the most studied region in this regard, with fairly conclusive results that lower BMD can be observed in cyclists compared with controls [29-35], practitioners of other sports [19,35-37] or reference values [4,38,39]. Moreover, the pelvic and hip regions, as key areas for osteoporotic fractures, and the whole body have been studied with concerning results.…”
Section: Resultsmentioning
confidence: 99%
“…Rector et al showed no differences between adult cyclists and runners in bone metabolism markers [37], and Guillaume et al reinforced that by showing these markers in normal ranges in a group of young cyclists [38]. However, Maïmoun et al [24] studied three groups of adult athletes (cyclists, triathletes and swimmers), compared to controls, and showed lower BAP in cyclists compared to any other group.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the short-term effects of different physical activities, including walking [ 37 , 38 ], outdoor jogging [ 39 ], aerobic exercise [ 28 , 40 , 41 ], resistance training [ 42 , 43 ] and cycling [ 27 , 44 , 45 ], on bone turnover. Gomes-Cabello et al summarized the effects of different training programs on bone turnover in a systematic review, and found that walking only modestly increased the loads on the skeleton above those caused by gravity; thus, this type of exercise does not effectively prevent osteoporosis in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulus of loading the musculoskeletal system through high-intensity dynamic sporting activity is proposed to compensate for 25[OH]D deficiency, with the absence of poor bone health in athletes [ 102 , 105 ]. However, non-weight-bearing athletes are prone to the same detrimental skeletal effects [ 104 , 106 ] and are at higher risk for low BMD when vitamin D status is low [ 107 109 ].…”
Section: Functional Roles Of Vitamin D Relevant To the Athletementioning
confidence: 99%